Jordan : Staff Report for the 2006 Article IV Consultation and Fourth Post-Program Monitoring Discussions. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This 2006 Article IV Consultation highlights that the Jordanian economy has performed remarkably well in recent years, mainly owing to far-reaching macroeconomic and structural reforms. Despite negative shocks, growth has been robust, inflation has remained low, public debt has continued to fall, and reserves have reached an all-time high. Economic performance remained strong in 2006. Growth is estimated at 6 percent for the year, reflecting buoyant domestic demand, in part financed by large private capital inflows. Average inflation was 6.3 percent, stemming mainly from fuel and imported food price increases.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet